Evaluation of Career Designing Competence of Young People with Disability in the Context of Knowledge-based Society - Rudžinskienė, Rasa; Rudokaitė, Judita (Socialinė teorija, empirija, politika ir praktika, 2014)
SummaryThe career designing competence of young people with disability has been analysed in this article. The concepts of career, career designing, and disability have been identified in this article. Research data has been collected using the semi-structured interview method. The quantitative research of young people with disability has been presented in this article in order to reveal the importance of career designing for successful career planning and development. Results of this research showed that young people are faced with various problems in choosing career paths or integrating into the labour market. Also, the peculiarities of young people career planning, realisation and management have been revealed in this article.Key words: career designing, disability, career, labour market.